2017
DOI: 10.1071/rd17046
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of polydatin on experimental testicular torsion and detorsion injury in rats

Abstract: Oxidative stress plays a critical role in the process of testicular torsion and detorsion (T/D). The purpose of the present study was to investigate the protective effect of polydatin (PD) on testicular T/D injury. Rats were randomly divided into three groups, a sham group, a group subjected to 2h torsion followed by 24h detorsion and a group subjected to T/D and injected i.p. with 20mgkg PD 30min before detorsion. Unilateral orchiectomy was performed after 24h of reperfusion. Half the testes were prepared for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Ischaemia/reperfusion (IR) injury plays an important role in the pathophysiology of TT and affects the degree of atrophy and sperm count (Abdel‐Rahman, Mahmoud, Mostafa, Saleh, & Eissa, ; Mertoğlu et al., ). High content of polyunsaturated fatty acids in the plasma membrane of sperms increases their vulnerability to ROS and oxidative stress (Qiao et al., ; Rifaioglu et al., ; Yuluğ et al., ). Based on previous evidences, early detection and treatment can improve the results of the treatment and patients’ quality of life (Amani et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ischaemia/reperfusion (IR) injury plays an important role in the pathophysiology of TT and affects the degree of atrophy and sperm count (Abdel‐Rahman, Mahmoud, Mostafa, Saleh, & Eissa, ; Mertoğlu et al., ). High content of polyunsaturated fatty acids in the plasma membrane of sperms increases their vulnerability to ROS and oxidative stress (Qiao et al., ; Rifaioglu et al., ; Yuluğ et al., ). Based on previous evidences, early detection and treatment can improve the results of the treatment and patients’ quality of life (Amani et al., ).…”
Section: Introductionmentioning
confidence: 99%
“… 21 At the same time, polydatin can also reduce the damage to the testis of mice caused by ionizing radiation by inhibiting the ratio of apoptosis-related protein Bcl-2/Bax. 40 All the above studies have shown that polydatin has a significant radiation protection effect, but for reproductive damage induced by ionizing radiation, more experimental studies are still needed to demonstrate its effective dose and action mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Testicular torsion desorption (T/D) is a common male disease, and the reduction of germ cells is inevitable. PD (20 mg/kg) significantly improved T/D‐related morphological injury, which increased the ratio of Bcl‐2/Bax to reduce apoptosis, reduced the level of MDA, and increased the expression of SOD to resist oxidation (Qiao et al, 2017). PD reduced arsenic‐induced lipid peroxidation and regenerated testicular tissue injury in rats (Ince et al, 2016).…”
Section: Pharmacological Effectsmentioning
confidence: 99%